An Investigation Study on Usage of Boric Powder and Ethylene Glycol Based Synthetic Boric Acid Polymer as Bitumen Modifiers - Chai, Zhen Hao (2015)
In this research ethylene glycol based synthetic boric acid polymer (EGBAP) and boric powder were used to improve the properties of 80/100 penetration grade bitumen. The ethylene glycol based synthetic boric acid polymer was synthesized in the laboratory. The percentage of additives used were 1%, 2%, 3%, 4% and 5% by weight of bitumen. High shear rate mixer was used for blending additive with bitumen. All blended samples were then tested using Empirical test namely Penetration, Softening Temperature and Ductility according to ASTM standard test methods. Morphological Analysis using Scanning Electron Microscope was done to know the compatibility of the polymer with bitumen. From the results, the penetration value of modified bitumen decreased and the softening point of modified bitumen increased. As a result, modification of bitumen with boric powder and ethylene glycol based synthetic boric acid polymer (EGBAP) induced stiffness thus would improve the fatigue resistance of pavement. Ductility of all modified bitumen was lower than virgin bitumen thus the modified bitumen might crack at low temperature. However, most of ductility of the modified bitumen was above the minimum requirement of 75cm for 80/100 penetration grade bitumen so the modified bitumen could be used in hot climatic country. The morphological analysis also reflected that the compatibility of modified bitumen was increased as proved by empirical test results.